PENGARUH KINERJA MENGAJAR GURU DAN IKLIM SEKOLAH TERHADAP PRESTASI BELAJAR SISWA (Studi Deskriptif di MI Kelompok Kerja Madrasah Cipaku) - Kholisoh, Lilis; Herman, Maman; Enas, Enas (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine: 1) The effect of teacher teaching performance on student achievement. 2) The influence of school climate on student achievement. 3) The effect of teacher teaching performance and school climate on student learning achievement. The research method used in the preparation of this scientific paper is descriptive. The unit of analysis is a school with a total of 171 respondents. The data were proceeded by using SPSS 17.0. The study results show that: 1) The teaching performance of teachers at MI KKM Cipaku is in high criteria, however, some indicators need to be improved, namely arranging seats according to the characteristics of students and subjects. Furthermore, the teacher's teaching performance has a positive effect on student achievement. This means that the higher the teacher's teaching performance, the higher the student's learning achievement. 2) The school climate at MI KKM Cipaku is in conducive criteria, however, some indicators need to be improved, namely monumental evidence of the results of the school's collaboration with the community. Furthermore, the school climate has a positive effect on student achievement. This means that the more conducive the school climate, the more students' learning achievement. 3) Student achievement at KKM Cipaku is in the achievement criteria, however, several indicators must be improved, namely youth scientific work, academic competitions, sports, arts, and scouts. Furthermore, teacher teaching performance and school climate have a positive effect on student learning achievement. This means that the higher the teacher's teaching performance and the more conducive the school climate, the higher the student's learning achievement.